2019
DOI: 10.1186/s40795-019-0314-7
|View full text |Cite
|
Sign up to set email alerts
|

Diet quality is associated with malnutrition and low calf circumference in Canadian long-term care residents

Abstract: Background: Older adults living in long-term care (LTC) are nutritionally vulnerable. The purpose of this study was to determine diet quality of Canadian LTC residents and its association with malnutrition and low calf circumference. Methods: A cross-sectional study was undertaken in 32 LTC homes across four Canadian provinces. Nutrient adequacy ratios (NARs) were calculated for seventeen nutrients; mean adequacy ratio (MAR) was calculated to describe overall diet quality. Malnutrition risk was assessed with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 44 publications
0
11
0
1
Order By: Relevance
“…In the same study, older adults with better dietary quality and habits were more likely to have better nutritional status. In addition, a US longitudinal study showed that malnutrition was significantly associated with poorer diet quality and lower energy and protein intake ( 60 ).…”
Section: Methodsmentioning
confidence: 99%
“…In the same study, older adults with better dietary quality and habits were more likely to have better nutritional status. In addition, a US longitudinal study showed that malnutrition was significantly associated with poorer diet quality and lower energy and protein intake ( 60 ).…”
Section: Methodsmentioning
confidence: 99%
“…Eine Malnutrition ist wiederum ein bedeutsamer Risikofaktor für eine erhöhte Morbidität und Mortalität, insbesondere während und nach Hospitalisierungsphasen [18]. Einfach durchzuführende Maßnahmen zur Beurteilung des Ernährungsstatus sind: ▪ Bestimmung des BMI ▪ Messungen; Messung des Wadenumfangs von < 31 cm oder Oberarmumfangs (bei Beinödemen) von < 21 cm sprechen für Mangelernährung [19].…”
Section: Ernährungsstatusunclassified
“…Also essential, and yet we did not find any study focusing on it, is the quality of food (nutritious aspects) of the meals sold at transport stations. Eating a well nourishing diet or balanced meals is critical to ensure good health [43][44][45] ; hence, we encourage future primary studies to include the nutritious aspects. Such studies may help streamline guidelines or inform policies to improve the quality of the food sold at transport exchange sites or taxi ranks.…”
Section: Study Key Findings Reportedmentioning
confidence: 99%